Evaluación del funcionamiento técnico del horno de cubilote en la fundición de hierro de la Empresa Centro Mecanizado Pérez de la ciudad de Ambato para la mejora de la eficiencia térmica. Propuesta de reformas técnicas al horno. - Tirado Gallo, Inés Georgina (2018)
Based on the experimental information, the operational parameters of the cupola furnace for the smelting of gray iron at constant pressure of the Company Centro Mecanizado Pérez in Ambato were found. Transfer losses, combustion efficiency and melting efficiency values were determined, these efficiencies were evaluated for the cupola furnace with coke as the sole energy carrier, and the efficiency improvement was analyzed by simulation in FEM "ANSYS Academic Student" software using the ANSYS CFD module, which is the fluent. Based on the results of the comparisons, the research shows that the installation of an air heating chamber before entering the wind chamber in the cupola furnace leads to a reduction in the consumption of coke and, in addition, a reduction in the emission of polluting gases. The adoption of the air heating chamber will be beneficial for the company in terms of energy savings and cost reduction. It was verified that the change of the operational parameter of the air inlet temperature to the cupola furnace wind box improves the melting and combustion efficiency as indicated by the bibliographic analysis of research works by (Golón, 2009) and (Lee., 2003). Finally, the environmental impact before and after the improvement to the cupola furnace was analyzed, finding a decrease in the emission of contaminating gases.